Cardiac Arrhythmias - Lakshmanadoss, Umashankar (IntechOpen, 2018)
This book is a comprehensive and practical updated review about the various aspects of cardiac arrhythmias. It covers a variety of aspects of both atrial and nonatrial arrhythmias, including genetics, clinical aspects, ECG manifestations, and practical approaches to complex cardiac arrhythmia management - office, hospital, intensive care unit, electrophysiology laboratory, and operating room. This book also presents comprehensive ECG reviews of cardiac arrhythmias like atrial flutter, Brugada pattern, Breijo ECG pattern, and PVCs. Practical aspects of preventing and managing arrhythmias - central venous catheter-induced, atrial flutter, and drug-induced cardiac arrhythmias - are described. Experts have demonstrated the approach for mapping and ablation of complex arrhythmias like atrial flutter, idiopathic ventricular tachycardia, and Brugada syndrome.